Rozwiąż równanie metodą podstawiania
[tex]3tgx+3ctgx=4\sqrt{3}[/tex]


Odpowiedź :

Rozwiązanie:

[tex]3tgx+3ctgx=4\sqrt{3} \\cosx\neq 0 \wedge sinx\neq 0\\x\neq \frac{\pi }{2}+2k\pi \wedge x\neq k\pi \\3tgx+\frac{3}{tgx} =4\sqrt{3}[/tex]

Niech [tex]t=tgx[/tex] :

[tex]3t+\frac{3}{t}=4\sqrt{3} \\3t^{2}-4\sqrt{3}t+3=0\\\Delta_{t}=48-4*3*3=12\\t_{1}=\frac{4\sqrt{3}-2\sqrt{3} }{6} =\frac{\sqrt{3} }{3}\\t_{2}= \frac{4\sqrt{3}+2\sqrt{3} }{6} =\sqrt{3}[/tex]

Wracamy do [tex]x[/tex]:

[tex]tgx=\frac{\sqrt{3} }{3} \vee tgx=\sqrt{3}\\x=\frac{\pi }{6}+k\pi \vee x=\frac{\pi }{3}+k\pi[/tex]